Transformasi Kurikulum di Era Globalisasi: Keterbatasan Sarana dan Prasarana yang Mumpuni - Lesi Oktiani Putri; Alifia Mutsla Fakhruddin; Prihantini Prihantini (Universitas Palan, 2024)
Curriculum is the most important thing in education because curriculum is a guide and reference for the implementation of education. A good curriculum is a dynamic curriculum which is a curriculum that appropriate to the times and global conditions so that the curriculum will continue to change. The curriculum change process is a complicated process and requires preparation from various aspects. In the process of changing Kurikulum 2013 to Kurikulum Merdeka, school readiness is required, for example, the aspect of developing facilities and infrastructure. Facilities and infrastructure are very important in educational activities because they will really support students in learning.